Reallocation in the Great Recession: Cleansing or Not? - Foster, Lucia; Grim, Cheryl; Haltiwanger, John (Journal of Labor Economics, 2016)
The high pace of reallocation across producers is pervasive in the US economy. Evidence shows that this high pace of reallocation is closely linked to productivity. While these patterns hold on average, the extent to which the reallocation dynamics in recessions are “cleansing” is an open question. We find that downturns prior to the Great Recession are periods of accelerated reallocation even more productivity enhancing than reallocation in normal times. In the Great Recession, we find that the intensity of reallocation fell rather than rose and that the reallocation that did occur was less productivity enhancing than in prior recessions.